Dual role of B7 costimulation in obesity-related nonalcoholic steatohepatitis and metabolic dysregulation - Chatzigeorgiou, Antonios; Chung, Kyoung-Jin; Garcia-Martin, Ruben; Alexaki, Vasileia-Ismini; Klotzsche-von Ameln, Anne; Phieler, Julia; Sprott, David; Kanczkowski, Waldemar; Tzanavari, Theodora; Bdeir, Mohktar; Bergmann, Sibylle; Cartellieri, Marc; et al. (Wiley, 2014)
The low-grade inflammatory state present in obesity contributes to obesity-related metabolic dysregulation, including nonalcoholic steatohepatitis (NASH) and insulin resistance. Intercellular interactions between immune cells or between immune cells and hepatic parenchymal cells contribute to the exacerbation of liver inflammation and steatosis in obesity. The costimulatory molecules, B7.1 and B7.2, are important regulators of cell-cell interactions in several immune processes; however, the role of B7 costimulation in obesity-related liver inflammation is unknown. Here, diet-induced obesity (DIO) studies in mice with genetic inactivation of both B7.1 and B7.2 (double knockout; DKO) revealed aggravated obesity-related metabolic dysregulation, reduced insulin signalling in the liver and adipose tissue (AT), glucose intolerance, and enhanced progression to steatohepatitis resulting from B7.1/B7.2 double deficiency. The metabolic phenotype of B7.1/B7.2 double deficiency upon DIO was accompanied by increased hepatic and AT inflammation, associated with largely reduced numbers of regulatory T cells (Tregs) in these organs. In order to assess the role of B7 costimulation in DIO in a non-Treg-lacking environment, we performed antibody (Ab)-mediated inhibition of B7 molecules in wild-type mice in DIO. Antibody-blockade of both B7.1 and B7.2 improved the metabolic phenotype of DIO mice, which was linked to amelioration of hepatic steatosis and reduced inflammation in liver and AT. Conclusion: Our study demonstrates a dual role of B7 costimulation in the course of obesity-related sequelae, particularly NASH. The genetic inactivation of B7.1/B7.2 deteriorates obesity-related liver steatosis and metabolic dysregulation, likely a result of the intrinsic absence of Tregs in these mice, rendering DKO mice a novel murine model of NASH. In contrast, inhibition of B7 costimulation under conditions where Tregs are present may provide a novel therapeutic approach for obesity-related metabolic dysregulation and, especially, NASH